The effect of dual antiplatelet therapy for improvement of extracranial and intracranial artery stenosis evaluated by digital subtraction angiography - Usman, Fritz S.; Sinaga, Rony Parlindungan; Dewi, Karina; Nilamsari,; Rasyid, Daril Al; Kastilong, Merlin P. (International Journal of Research in Medical Sciences, 2024)
Background: Stroke involving extracranial carotid (ECAS), vertebral (EVAS), and intracranial arteries (IAS) contributed to an annual stroke rate of 0.1-3.3%. Even though endarterectomy and/or angioplasty and stenting had revolutionized its’ management, best medical treatment (BMT) is still the mainstay of therapy to prevent secondary stroke/transient ischemic attack. This study aimed to evaluate the effect of BMT to reduce the degree of stenosis by using six-months double antiplatelet therapy (DAPT). Methods: A retrospective cohort study was conducted in a secondary private hospital in Indonesia, in January-December 2022. Adults ≥18 years old with ECAS, EVAS, or IAS detected using digital subtraction angiography (DSA), receiving DAPT for at least six months, and those who had second DSA evaluation were included. Any subjects with other brain pathologies or recorded incompliance to DAPT were excluded. Age, gender, stenosis degree, stenosis location, and conversion of stenosis degree were recorded and compared between pre-DAPT and post-DAPT group. Results: Of 30 subjects, there were insignificant changes (46.5±24.3% to 50.8±22.9%, p=0.09) of ECAS, EVAS, and IAS. There were 14 cases with constant stenosis (51.4±17.5%), 8 cases with decreasing stenosis (46.9±28.2% to 40.1±32.8%, p=0.012), and 12 cases with increasing stenosis (40.4±29.9% to 57.1±21.0%, p=0.002). No significant association were found among those groups related to traditional vascular risk factors. Conclusions: There was no difference in respect to the degree of stenosis following six months of DAPT in either ECAS, EVAS, or IAS. Routine evaluation as well as recognizing features of high-risk stroke/TIA are important to help decide individual who may be candidates of endovascular procedures earlier.